2009
DOI: 10.1152/jn.90829.2008
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Oscillations in the Cerebellar Cortex of the Tottering Mouse

Abstract: EJ, Ebner TJ. Low-frequency oscillations in the cerebellar cortex of the tottering mouse. J Neurophysiol 101: 234 -245, 2009. First published November 5, 2008 doi:10.1152/jn.90829.2008. The tottering mouse is an autosomal recessive disorder involving a missense mutation in the gene encoding P/Q-type voltage-gated Ca 2ϩ channels. The tottering mouse has a characteristic phenotype consisting of transient attacks of dystonia triggered by stress, caffeine, or ethanol. The neural events underlying these episodes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 84 publications
(115 reference statements)
10
72
0
Order By: Relevance
“…Similar to the imaging studies in patients, abnormal cerebellar function is observed in genetic mouse and rat models of dystonia (LeDoux and Lorden, 2002;Chen et al, 2009;Zhang et al, 2011). Indeed, an increase in metabolic activity in the cerebellum is observed in mouse models of DYT1 dystonia (Ulug et al, 2011;Zhao et al, 2011), similar to imaging studies in DYT1 patients.…”
Section: Introductionsupporting
confidence: 73%
“…Similar to the imaging studies in patients, abnormal cerebellar function is observed in genetic mouse and rat models of dystonia (LeDoux and Lorden, 2002;Chen et al, 2009;Zhang et al, 2011). Indeed, an increase in metabolic activity in the cerebellum is observed in mouse models of DYT1 dystonia (Ulug et al, 2011;Zhao et al, 2011), similar to imaging studies in DYT1 patients.…”
Section: Introductionsupporting
confidence: 73%
“…The [Ca 2+ ] c plays important roles in controlling neuronal excitability, synaptic plasticity and gene activation, and its dysregulation is associated with a variety of neurological disorders including epilepsy [28], Huntington's disease [21] and Alzheimer's disease [43]. Ca 2+ overload could potentially lead to neuronal dysfunction in the context of dystonia In support of this notion, in vivo administration of L-type Ca 2+ channel agonists or caffeine induce dystonia-like movements in rodents [6,7,17]. Additionally, a recent study demonstrated that Ca 2+ regulation in the peripheral neurons is abnormal in dystonia musculorum, an autosomal-recessive neurodegenerative disease in mouse that is characterized by progressive ataxia and sensory neuropathy [33].…”
Section: Discussionmentioning
confidence: 98%
“…Details of animal preparation and experimental setup have been described in previous publications 24,26,27 . For some experiments mice were anesthetized by intramuscular injection of a cocktail of ketamine (60 mg/kg), xylazine (3 mg/kg) and acepromazine (1.2 mg/kg), placed in a stereotaxic frame, mechanically ventilated and body temperature feedback-regulated.…”
Section: Animal Breeding and Preparationmentioning
confidence: 99%
“…Imaging flavoprotein autofluorescence used a band pass excitation filter (455 ± 35 nm), an extended reflectance dichroic mirror (500 nm), and a > 515 nm long pass emission filter 24 . Additional imaging procedures for the awake mouse were described in a previous publication 27 . Caffeine (10-15 mg/kg, I.P.)…”
Section: Optical Imagingmentioning
confidence: 99%
See 1 more Smart Citation